Association of Dental Infections with Intracranial Atherosclerotic Stenosis - Sen, Souvik; Meyer, Jaclyn; Mascari, Rachel; Trivedi, Tushar; Suri, Fareed; Wasserman, Bruce; Rosamond, Wayne; Moss, Kevin; Beck, James; Gottesman, Rebecca F (Cerebrovascular diseases (Basel, Switzerland), 2024)
Periodontal disease (PD) and dental caries are oral infections leading to tooth loss that are associated with atherosclerosis and cerebrovascular disease. We assessed the hypothesis that PD and caries are associated with asymptomatic intracranial atherosclerosis (ICAS) in the Atherosclerosis Risk in Communities (ARIC) study. Full-mouth clinical periodontal measurements (7 indices) collected at 6 sites per tooth from 6,155 subjects from the Dental Atherosclerosis Risk in Communities Study (DARIC) without prior stroke were used to differentiate seven PD stages (Periodontal Profile Class [PPC]-I to -VII) and dental caries on coronal dental surface (DS) and dental root surface (DRS). A stratified subset underwent 3D time-of-flight MR angiogram and 3D high isotropic-resolution black blood MRI. ICAS was graded according to the criteria established by the Warfarin-Aspirin Symptomatic Intracranial Disease (WASID) trial. We evaluated the relationship between PD stage and dental caries with asymptomatic ICAS, graded as no ICAS, <50% ICAS, and ≥50% ICAS. Among dentate subjects who underwent vascular imaging, 801 (70%) had no ICAS, 232 (20%) had <50% ICAS, and 112 (10%) had ≥50% ICAS. Compared to participants without gum disease (PPC-I), participants with mild-moderate tooth loss (PPC-VI), severe tooth loss (PPC-VII), and severe PD (PPC-IV) had higher odds of having <50% ICAS. Participants with extensive gingivitis (PPC-V) had significantly higher odds of having ≥50% ICAS. This association remained significant after adjusting for confounding variables: age, gender, race, hypertension, diabetes, dyslipidemia, 3-level education, and smoking status. There was no association between dental caries (DS and DRS) and ICAS <50% and ≥50%. We report significant associations between mild-moderate tooth loss, severe tooth loss, and severe PD with <50% ICAS as well as an association between extensive gingivitis and ≥50% ICAS. We did not find an association between dental caries and ICAS.